Gender, Sexuality and Transitional Change in Czech Popular Literature - Kos, Suzana, bohemistica (2013)
After the fall of communism Czech literary scene had to deal with two phenomena - on the one hand, a serious revision of near half-a-century literary production was in need, and at the same time, there occurred a significant number of new literary theories coming from the West, new literary genres emerged, and popular literature appeared to be in bloom. In the words of Angela McRobbie, „ relations of power are indeed made and re-made within texts of enjoyment and rituals of relaxation and abandonment.“ (McRobbie, Angela, The Aftermath of Feminism, 2009) This is the reason why I chose the prose texts of Czech authors whose works were branded as „popular fiction“ to examine in which way they take part in the new distribution of gender power in the transitional society, as the Czech one. The article will also treat these texts as the testament of the transitional change, and explore its most prominent features, such as loss of identity, consumerism and rise of new political structures, all of which contribute to the distribution of power in today's society.